A Meta-Analysis of Working Memory Deficits in Children With Learning Difficulties: Is There a Difference Between Verbal Domain and Numerical Domain?. (January 2016) - Peng, Peng; Fuchs, Douglas
Children with learning difficulties suffer from working memory (WM) deficits. Yet the specificity of deficits associated with different types of learning difficulties remains unclear. Further research can contribute to our understanding of the nature of WM and the relationship between it and learning difficulties. The current meta-analysis synthesized research on verbal WM and numerical WM among children with reading difficulties (RD), children with mathematics difficulties (MD), and children with reading and mathematics difficulties (RDMD). A total of 29 studies subsuming 110 comparisons were included. Results showed that compared to typically developing children, all learning difficulty groups demonstrated deficits in verbal WM and numerical WM, with RDMD children showing the most severe WM deficits. MD children and RD children showed comparable verbal WM deficits, but MD children showed more severe numerical WM deficits than RD children. Neither severity of learning difficulties nor type of academic screening emerged as a moderator of WM deficit profiles. Although the findings indicate the domain-general nature of WM deficits in RD, MD, and RDMD children, the numerical WM deficits of children with MD and RDMD may reflect the domain-specific nature of WM deficits.